Sodium ferrous citrate and preparation method thereof
By reacting in an inert atmosphere and filtration in an ethanol solution, the problem of high cost and low purity in the preparation process of sodium ferrous citrate in the prior art is solved, and an efficient and environmentally friendly preparation process is achieved, satisfying the Medicinal quality standards.
Patent Information
- Application Number
- CN202310004682.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-03
AI Technical Summary
The existing preparation methods for sodium ferrous citrate have high production costs and low purity, and a large number of by-products are generated during the reaction, which increases the burden of three waste treatment and environmental pollution.
The reaction was carried out in an inert atmosphere to prevent the oxidation of ferrous ions, and the reaction product was refluxed in the ethanol solution and filtered while hot, significantly improving the purity and yield of the target product.
Through this method, the yield and purity of sodium ferrous citrate is improved, production costs are reduced, environmental pollution is reduced, and the quality standards of various countries are met.
Smart Images

Figure CN116063173B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical pharmacy, and in particular to sodium ferrous citrate and a preparation method thereof. Background Art
[0002] Sodium ferrous citrate is a complex drug of sodium citrate and divalent iron, used for oral administration to treat iron deficiency anemia. It was first marketed in Japan in 1986. The ammonium ferric citrate and sodium ferric citrate in the early ferric citrate complex drugs used to treat iron deficiency anemia are both generated from trivalent iron and poorly absorbed in the body, while the divalent iron complex is easy to dissolve and absorb, and the utilization rate of iron is high. Its molecular formula is Na 4 [Fe(C 6 H 8 O 7 ) 2 ], the structural formula is as follows:
[0003]
[0004] The method described by Sun Rupin et al. in the preparation of sodium ferrous citrate (Chinese Journal of Pharmaceutical Industry, 1994 (12): 534-535.) is to use trisodium citrate and ferrous sulfate or ferrous chloride as raw materials, react at high temperature, and then treat with denatured ethanol to obtain sodium ferrous citrate. Japanese patent JPS58172343 also discloses a similar method, which will generate a large amount of by-products of sodium sulfate or sodium chloride, increasing the burden of three wastes treatment; and after the reaction is completed, a large amount of denatured ethanol or methanol is used to treat the product, the amount of organic solvent used is large, and it is difficult to recover. The treatment process is cumbersome, which increases the cost and also causes pollution to the environment.
[0005] The method described in the prior art CN114436811A is roughly the same as the method in JPS58172343, both of which use sodium citrate and ferrous sulfate as raw materials for reaction, except that an appropriate amount of sodium sulfite is added during the reaction, but the post-processing method is to filter and collect the filtrate for concentration to obtain sodium ferrous citrate. Through experimental comparison, the filtrate obtained by the production method has an extremely low yield after concentration, and trivalent iron and sulfate are seriously exceeded.
[0006] Therefore, there is an urgent need to provide a new method for preparing sodium ferrous citrate to solve the problems of high production cost and low purity in the existing preparation methods. Summary of the invention
[0007] The invention aims to provide sodium ferrous citrate and a preparation method thereof, wherein the reaction process is strictly controlled to be carried out in an inert atmosphere to prevent oxidation of ferrous ions, and then the reaction product is refluxed in an ethanol solution and filtered while hot, thereby significantly improving the purity and yield of the target product.
[0008] To achieve the above object, the present invention provides a method for preparing sodium ferrous citrate, comprising:
[0009] (1) adding an aqueous ferrous sulfate solution to an aqueous sodium citrate solution, and adding ascorbic acid, replacing the reaction system with an inert gas environment, heating the reaction, cooling and centrifuging to obtain a crude sodium ferrous citrate product;
[0010] (2) The crude sodium ferrous citrate product is heated to reflux in 75%-95% ethanol by mass, and then filtered while hot, and the filter cake is rinsed and dried to obtain sodium ferrous citrate. Reflux in an alcohol-water solution will not cause a large amount of sodium ferrous citrate to dissolve and reduce the yield, and impurities that are easily soluble in ethanol or water can be dissolved and removed, thereby obtaining sodium ferrous citrate that meets the internal control standard.
[0011] Furthermore, the heating reflux temperature is 75-80°C and the time is 10-30 minutes.
[0012] Preferably, the crude sodium ferrous citrate product is heated to reflux in 85% by mass ethanol for 15 to 20 minutes.
[0013] Furthermore, the amount of ethanol used is 2 to 5 times the mass of the crude sodium ferrous citrate product, preferably 2.5 to 3.0 times.
[0014] Furthermore, the temperature of the high temperature reaction is 80°C to 110°C, preferably 90°C to 110°C, and more preferably 95°C to 105°C; and the heating reaction time is 2 to 4 hours.
[0015] And / or, the dissolution temperature of the sodium citrate aqueous solution is 85-110°C, preferably 95-105°C.
[0016] Furthermore, the method for preparing the ferrous sulfate aqueous solution comprises: adding iron powder into dilute sulfuric acid in batches, then adding ferrous sulfide, and filtering after the reaction is complete to obtain the ferrous sulfate aqueous solution.
[0017] The invention uses cheap iron powder and sulfuric acid as raw materials, utilizes inert gas protection to prevent ferrous ions from being oxidized, prepares ferrous sulfate solution, and then reacts the ferrous sulfate solution with sodium citrate. Through strict process parameter control, the reaction yield can be increased to 88-95%, thereby reducing production costs.
[0018] Furthermore, the molar feed ratio of the iron powder to sodium citrate is 1.0:(2.0-3.0), preferably 1.0:(2.3-2.5).
[0019] Furthermore, the molar feed ratio of the iron powder to the dilute sulfuric acid is (1.0-1.3):1.0, preferably (1.05-1.1):1.0;
[0020] And / or, the concentration of the dilute sulfuric acid is 5 to 20 wt %, preferably 10 to 15 wt %.
[0021] Furthermore, the amount of ferrous sulfide is 0.5% to 2.0wt% of the amount of iron powder, preferably 0.8% to 1.0wt%. Metallic impurities (cobalt, nickel, zinc, etc.) are mainly introduced from ferrous sulfate. When preparing ferrous sulfate solution, the present invention uses reduced iron powder and sulfuric acid with high purity, and adds an appropriate amount of ferrous sulfide, which can form precipitation with metal elements such as cobalt, nickel and zinc during the reaction process, and is removed by filtering, thereby ensuring the limit control of elemental impurities in the product.
[0022] Furthermore, the amount of ascorbic acid added is 0.3-1% of the mass of the iron powder. In the present invention, inert gas is added to protect the reaction during the reaction, and an appropriate amount of ascorbic acid is added as an antioxidant to prevent ferrous ions from being oxidized to trivalent iron. After the crude sodium ferrous citrate is obtained, a certain mass fraction of ethanol is further used for refining, thereby avoiding the residual trivalent iron impurities, thereby greatly improving the purity of the product.
[0023] In some specific embodiments, the method is prepared by the following steps:
[0024] Step 1), dissolving sodium citrate in an appropriate amount of purified water at high temperature to prepare a sodium citrate aqueous solution;
[0025] Step 2), adding iron powder to dilute sulfuric acid in batches, adding an appropriate amount of ferrous sulfide, and filtering after the reaction is complete to obtain a ferrous sulfate aqueous solution;
[0026] Step 3), adding the ferrous sulfate aqueous solution to the sodium citrate aqueous solution, and adding an appropriate amount of ascorbic acid, replacing the reaction system with an inert gas environment, reacting at high temperature for 2 to 4 hours, cooling and centrifuging to obtain a crude sodium ferrous citrate product;
[0027] Step 4), treating the crude sodium ferrous citrate product with ethanol to obtain high-purity sodium ferrous citrate.
[0028] Therefore, the present invention solves the problems of high production cost, high product impurities and low actual yield of target product in the existing preparation method through the above method. In addition, the present invention further shortens the reaction time and reduces the production cost by adjusting the reaction temperature; through inert gas protection reaction and ethanol refining, the target product content and the actual yield of the target product are increased, and the content of trivalent iron impurities is further reduced.
[0029] To achieve the above object, the present invention also provides sodium ferrous citrate, which is prepared by any of the preparation methods described above.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The preparation method of sodium ferrous citrate provided by the present invention strictly controls the reaction process to be carried out in an inert atmosphere, thereby preventing the oxidation of ferrous ions; and then the reaction product is refluxed in an ethanol solution to dissolve and remove impurities that are easily soluble in ethanol or water, thereby obtaining sodium ferrous citrate that meets the internal control standard.
[0032] 2. The present invention uses iron powder, sulfuric acid and sodium citrate as raw materials, and the solvents are purified water and ethanol. The ethanol can be recycled and reused, and the total yield is 88% to 95%, and the production cost is low. The iron content of the sodium ferrous citrate produced by the present invention is 10.0 to 11.0%, the trivalent iron content is less than 0.1%, the sulfate content is less than 0.5%, the chloride content is less than 0.1%, and the metal element impurities meet the requirements of the pharmacopoeias of various countries.
[0033] 3. The equipment used in the production of the present invention are all general production equipment, and the industrial feasibility is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is the infrared detection spectrum of sodium ferrous citrate.
[0036] Figure 2 This is the thermogravimetric analysis spectrum of sodium ferrous citrate.
[0037] Figure 3 This is the X-ray diffraction pattern of sodium ferrous citrate. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing sodium ferrous citrate comprises the following steps:
[0041] Step 1) Dissolve 1800 g of sodium citrate in 1800 g of purified water at 98°C.
[0042] Step 2) 140 g of iron powder was added to dilute sulfuric acid (245 g of concentrated sulfuric acid was diluted to 2450 mL) in batches, 1.4 g of ferrous sulfide was added, the mixture was stirred at room temperature for 2 h, and filtered to obtain an aqueous solution of ferrous sulfate.
[0043] Step 3) Add the ferrous sulfate aqueous solution to the sodium citrate aqueous solution, replace the nitrogen environment of the reaction system, add 1.4 g of ascorbic acid, heat to 99 ° C for 2 hours, cool to 25 ° C, centrifuge, rinse the filter cake with 200 mL of purified water, collect the filter cake, and obtain crude sodium ferrous citrate.
[0044] Step 4) The crude product was added to a reaction flask, ethanol (3.3 kg, 85%) preheated to 65°C was added, the temperature was continued to rise to 79°C, refluxed for 15 minutes, filtered while hot, the filter cake was rinsed with 200 mL of ethanol, and vacuum dried at 45°C for 3 hours to obtain 1172 g of light green crystalline powder with a yield of 89.1%. The iron content was 10.6%, the trivalent iron content was 0.04%, the sulfate content was ≤0.3%, the chloride content was ≤0.1%, the nickel content was 4.2 ppm, the cobalt content was 1.0 ppm, and the zinc content was 0.2 ppm.
[0045] Example 2
[0046] A method for preparing sodium ferrous citrate comprises the following steps:
[0047] Step 1) Dissolve 180 g of sodium citrate in 180 g of purified water at 95°C.
[0048] Step 2) 14 g of iron powder was added to dilute sulfuric acid (23.5 g of concentrated sulfuric acid was diluted to 240 mL) in batches, and 0.12 g of ferrous sulfide was added. The mixture was stirred at room temperature for 2 h and filtered to obtain an aqueous solution of ferrous sulfate.
[0049] Step 3) adding the ferrous sulfate aqueous solution to the sodium citrate aqueous solution, replacing the nitrogen environment of the reaction system, adding 0.08 g of ascorbic acid, heating to 102 ° C for 2 hours, cooling to 20 ° C, centrifuging, rinsing the filter cake with 20 mL of purified water, and collecting the filter cake, i.e., crude sodium ferrous citrate.
[0050] Step 4) The crude product was added to a reaction flask, ethanol (340 mL, 85%) preheated to 65°C was added, the temperature was continued to rise to 79°C, refluxed for 15 minutes, filtered while hot, the filter cake was rinsed with 20 mL of ethanol, and vacuum dried at 45°C to obtain 119 g of light green crystalline powder with a yield of 90.5%. The iron content was 10.5%, the trivalent iron content was 0.03%, the sulfate content was ≤0.3%, the chloride content was ≤0.1%, the nickel content was 3.6 ppm, the cobalt content was 0.9 ppm, and the zinc content was 0.4 ppm.
[0051] On the basis of Example 1, the feeding amounts of ferrous sulfide and ascorbic acid were reasonably adjusted in Example 2, the yield difference was small, and the quality of the obtained products met the quality standard requirements.
[0052] Example 3
[0053] A method for preparing sodium ferrous citrate comprises the following steps:
[0054] Step 1) Dissolve 200 g of sodium citrate in 200 g of purified water at 100°C.
[0055] Step 2) 15.2 g of iron powder was added in batches to dilute sulfuric acid (24.1 g of concentrated sulfuric acid was diluted to 160 mL), 0.12 g of ferrous sulfide was added, the reaction was stirred at room temperature for 2 h, and filtered to obtain an aqueous solution of ferrous sulfate.
[0056] Step 3) adding the ferrous sulfate aqueous solution to the sodium citrate aqueous solution, replacing the nitrogen environment of the reaction system, adding 0.08 g of ascorbic acid, heating to 105° C. for 2 hours, cooling to 20-30° C., centrifuging, rinsing the filter cake with 25 mL of purified water, and collecting the filter cake, i.e., crude sodium ferrous citrate.
[0057] Step 4) The crude product was added to a reaction flask, ethanol (425 mL, 85%) preheated to 65°C was added, the temperature was continued to rise to 75°C, refluxed for 15 minutes, filtered while hot, the filter cake was rinsed with 25 mL of ethanol, and vacuum dried at 50°C to obtain 135.6 g of light green crystalline powder with a yield of 95.0%. The iron content was 10.5%, the trivalent iron content was 0.03%, the sulfate content was ≤0.3%, the chloride content was ≤0.1%, the nickel content was 3.8 ppm, the cobalt content was 1.2 ppm, and the zinc content was 0.5 ppm.
[0058] On the basis of Example 1, the feeding ratio of sodium citrate was increased in Example 3, and the product quality met the requirements and the yield was stable.
[0059] like Figure 1-3 As shown, it is shown that the present invention successfully prepares sodium ferrous citrate. Figure 2 The residual amount after medium heat weight loss is 54.6910%, which is mainly iron, sodium and pyrolysis residual carbon, while the total content of iron and sodium in sodium ferrous citric acid is about 28.3wt%. It can be seen that the pyrolysis residual rate of citric acid is also high, indicating good thermal stability. Figure 3 The upper middle figure is the actual diffraction pattern, and the lower figure is the diffraction angle of the maximum diffraction peak simulated according to different diffraction angles.
[0060] Example 4: Effect of the molar feed ratio of iron powder to sodium citrate
[0061] Example 4-1
[0062] A method for preparing sodium ferrous citrate, adopting the same method as that in Example 3, changing the molar feeding ratio of iron powder to sodium citrate to 1.0:2.3, obtaining 117.4 g of sodium ferrous citrate after reaction, with a yield of 82.2%, a reduced yield, an iron content of 10.4%, a trivalent iron content of 0.04%, a sulfate content of ≤0.3%, a chloride content of ≤0.1%, a nickel content of 4.0 ppm, a cobalt content of 1.3 ppm, and a zinc content of 0.4 ppm, which meets the quality standard requirements.
[0063] Example 4-2
[0064] The same method as Example 4-1 was adopted, except that the molar feeding ratio of iron powder to sodium citrate was changed to 1.0:2.5. After the reaction, 129.9 g of sodium ferrous citrate was obtained with a yield of 91.0%, an iron content of 10.3%, a trivalent iron content of 0.04%, sulfate ≤0.3%, chloride ≤0.1%, a nickel content of 4.1 ppm, a cobalt content of 1.4 ppm, and a zinc content of 0.6 ppm, which met the quality standard requirements.
[0065] Conclusion: Through the experimental results of Examples 3 and 4, it can be clearly seen that by controlling the molar feed ratio of iron powder to sodium citrate to 1.0:(2.0-3.0), sodium ferrous citrate that meets the internal control standard can be obtained.
[0066] Example 5: Effect of the molar feed ratio of iron powder to sulfuric acid
[0067] Example 5-1
[0068] The same method as in Example 3 was adopted, and the molar feed ratio of iron powder to sulfuric acid was changed to 1.0:1.0. After the reaction, 125.8 g of sodium ferrous citrate was obtained, with a yield of 88.1%, an iron content of 10.4%, a ferric iron content of 0.09%, sulfate ≤0.3%, chloride ≤0.1%, a nickel content of 4.0 ppm, a cobalt content of 1.1 ppm, and a zinc content of 0.4 ppm, which met the quality standard requirements. Among them, the ferric iron content was 0.09%, which was close to the 0.1% required by the quality standard.
[0069] Example 5-2
[0070] The same method as in Example 5-1 was used, except that the molar feed ratio of iron powder to sulfuric acid was changed to 1.05:1.0. After the reaction, 129.9 g of sodium ferrous citrate was obtained with a yield of 91.0%, an iron content of 10.3%, a trivalent iron content of 0.03%, a sulfate content of ≤0.3%, a chloride content of ≤0.1%, a nickel content of 3.9 ppm, a cobalt content of 1.2 ppm, and a zinc content of 0.5 ppm, which met the quality standard requirements.
[0071] Example 5-3
[0072] The same method as Example 5-1 was used, and the molar feed ratio of iron powder to sulfuric acid was changed to 1.3:1.0. After the reaction, 130.1 g of sodium ferrous citrate was obtained with a yield of 91.1%. The product quality met the standard requirements, and increasing the feed ratio of iron powder had little effect on the reaction.
[0073] Conclusion: Through the experimental results of Examples 5-1, 5-2, and 5-3, it can be clearly seen that by limiting the molar feed ratio of iron powder to sulfuric acid to (1.0-1.3):1.0, sodium ferrous citrate that meets the internal control standard can be produced.
[0074] Example 6: Effect of Ascorbic Acid Content
[0075] Example 6-1
[0076] The same method as in Example 3 was adopted, except that ascorbic acid was not added in step 3), and the obtained product had a ferric iron content of 0.36%, which exceeded the requirement of the pharmacopoeia limit standard.
[0077] Conclusion: Adding an appropriate amount of ascorbic acid as an antioxidant is beneficial to improving product quality.
[0078] Example 6-2
[0079] The same method as in Example 3 was used, except that the amount of ascorbic acid added in step 3) was 0.1% of the amount of iron powder added.
[0080] Product quality: The ferric iron content of the obtained product is 0.23%, which barely meets the limit standard of the pharmacopoeia, but seriously exceeds the internal control standard.
[0081] Example 6-3
[0082] The same method as in Example 3 was used, except that the amount of ascorbic acid added in step 3) was 0.3% of the amount of iron powder added.
[0083] Product quality: The ferric iron content of the obtained product is 0.09%, which is close to the limit of 0.1% specified in the internal control standard, indicating that the amount of ascorbic acid below 0.3% has a great risk of exceeding the ferric iron limit.
[0084] Example 6-4
[0085] The same method as in Example 3 was used, except that the amount of ascorbic acid added in step 3) was 1% of the amount of iron powder added.
[0086] Product quality: The ferric iron content of the obtained product is 0.05%, which means that the use of ascorbic acid exceeding 1.0% will not bring about further improvement of product quality and is unnecessary.
[0087] Conclusion: From the experimental results of Example 6-1, Example 6-2, Example 6-3, and Example 6-4, it can be clearly seen that when the amount of ascorbic acid added is 0.3-1% of the amount of iron powder added, sodium ferrous citrate that meets the internal control standard can be produced.
[0088] Example 7: Effect of ferrous sulfide content
[0089] Example 7-1
[0090] The same method as in Example 3 is adopted, except that ferrous sulfide is not added in step 2).
[0091] Product quality: The cobalt (Co) content of the produced sodium ferrous citrate is 5.13ppm, the nickel (Ni) content is 26.8ppm, and the zinc (Zn) content is 25.4ppm, which exceeds the requirements of the pharmacopoeia limit standards.
[0092] Example 7-2
[0093] The same method as in Example 3 is adopted, except that ferrous sulfide is added in step 2), and the feeding amount of ferrous sulfide is 0.5% of the feeding amount of iron powder.
[0094] Product quality: The cobalt (Co) content of the produced sodium ferrous citrate is 3.1ppm, the nickel (Ni) content is 8.2ppm, and the zinc (Zn) content is 3.3ppm, which meets the requirements of the pharmacopoeia limit standards.
[0095] Example 7-3
[0096] The same method as in Example 3 is adopted, except that ferrous sulfide is added in step 2), and the feeding amount of ferrous sulfide is 0.3% of the feeding amount of iron powder.
[0097] Product quality: The cobalt (Co) content of the produced sodium ferrous citrate is 5.8ppm, the nickel (Ni) content is 9.7ppm, and the zinc (Zn) content is 4.5ppm. The cobalt content is slightly higher than the standard requirement of 5ppm, and the nickel content is close to the standard requirement of 10ppm.
[0098] Example 7-4
[0099] The same method as in Example 3 is adopted, except that ferrous sulfide is added in step 2), and the feeding amount of ferrous sulfide is 2.0% of the feeding amount of iron powder.
[0100] Product quality: The cobalt (Co) content of the produced sodium ferrous citrate is 2.0ppm, the nickel (Ni) content is 3.7ppm, and the zinc (Zn) content is 2.7ppm, which meets the requirements of the pharmacopoeia limit standard. This shows that the use of iron powder exceeding 2.0% does not bring further improvement in product quality and is unnecessary.
[0101] Conclusion: Through the experimental results of Example 7-1, Example 7-2, Example 7-3, and Example 7-4, it can be clearly seen that the reasonable addition of ferrous sulfide can reduce the heavy metal limit of the final product, and the ratio of the amount of ferrous sulfide to the amount of iron powder is limited to 0.5% to 2.0%, and sodium ferrous citrate that meets the internal control standard can be obtained. A dosage exceeding 2.0% does not significantly improve the quality of the product.
[0102] Example 8: Effect of ethanol concentration on reflux effect
[0103] Example 8-1
[0104] The same method as in Example 3 was used, except that 75% ethanol was used in step 4) for treatment, and the amount used remained unchanged.
[0105] Product quality: The content of trivalent iron in the obtained product is 0.10%, the yield is 89.7%, and the quality meets the standard requirements.
[0106] Example 8-2
[0107] The same method as in Example 8-1 was used, except that 95% ethanol was used in step 4) for treatment, and the amount used remained unchanged.
[0108] Product quality: The content of trivalent iron in the obtained product is 0.04%, the yield is 93.6%, and the quality meets the requirements of the pharmacopoeia.
[0109] Example 8-3
[0110] The same method as in Example 8-1 was used, except that 60% ethanol was used in step 4) for treatment, and the amount used remained unchanged.
[0111] Product quality: The content of trivalent iron in the obtained product is 0.15%, and the quality does not meet the standard requirements.
[0112] in conclusion:
[0113] Through the experimental results of Example 8-1, Example 8-2, and Example 8-3, it can be clearly seen that in step 4), by limiting the concentration of ethanol added to 75%-95%, sodium ferrous citrate that meets the internal control standard can be obtained.
[0114] Example 9: Effect of Reflow Time
[0115] Example 9-1
[0116] The same method as in Example 3 was adopted, except that the reflux time in step 4) was 10 minutes. The trivalent iron content in the obtained product was 0.04%, the yield was 92.7%, and the quality met the standard requirements.
[0117] Example 9-2
[0118] The same method as in Example 3 was adopted, except that the reflux time in step 4) was 30 minutes. The trivalent iron content in the obtained product was 0.05%, and the yield was 90.9%. The yield was slightly reduced, the trivalent iron was slightly increased, and the quality met the standard requirements.
[0119] Example 9-3
[0120] The same method as in Example 3 was adopted, except that the reflux reaction temperature in step 4) was 70° C., and the ferric iron content in the obtained product was 0.24%, the yield was 93.3%, and the ferric iron content exceeded the standard limit requirement.
[0121] in conclusion:
[0122] The experimental results of Example 9-1, Example 9-2, and Example 9-3 clearly show that in step 4), by limiting the reaction temperature to reflux and the reaction time to 10 to 30 minutes, sodium ferrous citrate that meets the internal control standard can be obtained. When the temperature is not high enough to form reflux, it is not conducive to the dissolution and removal of impurities.
[0123] Example 10: Effect of the amount of ethanol added
[0124] Example 10-1
[0125] The same method as in Example 3 was adopted, except that the amount of ethanol added in step 4) was reduced by 2 times. The trivalent iron content in the obtained product was 0.09%, the yield was 91.3%, and the quality met the requirements of the pharmacopoeia.
[0126] Example 10-2
[0127] The same method as in Example 3 was adopted, except that the amount of ethanol added in step 4) was reduced by 2.5 times. The trivalent iron content in the obtained product was 0.05%, the yield was 93.4%, and the quality met the requirements of the pharmacopoeia.
[0128] Example 10-3
[0129] The same method as in Example 3 was adopted, except that the amount of ethanol added in step 4) was increased by 5 times. The trivalent iron content in the obtained product was 0.05%, the yield was 89.7%, and the quality met the requirements of the pharmacopoeia.
[0130] in conclusion:
[0131] The experimental results of Example 10-1, Example 10-2, and Example 10-3 clearly show that in step 4), when the amount of ethanol added is 2 to 5 times, sodium ferrous citrate that meets the internal control standard can be obtained.
[0132] Embodiment 11
[0133] The same method as step 1), step 2) and step 3) in Example 3 is adopted, except that the obtained crude sodium ferrous citrate is washed with 85% ethanol at 50° C. for 30 minutes and then dried. The trivalent iron content in the obtained product is 1.09%, which fails to meet the requirements of the internal control standard. It can be seen that the present invention can significantly reduce the content of trivalent iron by refluxing the ethanol solution.
[0134] Comparative Example 1
[0135] According to the synthesis method in JPS58172343, JP1982051129:
[0136] Take 29.4 g of sodium citrate dihydrate, add 44 mL of water, heat to 94°C and stir to dissolve.
[0137] Take 11.0 g of ferrous sulfate heptahydrate, add 22 mL of water, heat to 60°C and stir to dissolve.
[0138] Add ferrous sulfate solution to sodium citrate solution, heat to 90°C and stir to react for 2.5 hours, cool to 25°C, filter, rinse the filter cake with 30 mL of purified water, 30 mL of 50% ethanol aqueous solution, and 30 mL of ethanol in turn, collect the filter cake and dry it in vacuo at 50°C for 6 hours to obtain 17.7 g of light green crystals with a yield of 85.0%.
[0139] This method uses purified water, denatured ethanol, and ethanol to sequentially elute the crude sodium ferrous citrate product, which has a poor effect on removing ferric iron and easily leads to excessive ferric iron content in the product. The operation process is cumbersome, the amount of solvent is large, the cost is high, and the pollution to the environment is large.
[0140] Comparative Example 2
[0141] According to the synthesis method in CN114436811A:
[0142] Add 117 g of sodium citrate dihydrate and 200 mL of distilled water into the reaction flask and stir to dissolve;
[0143] Add 54 g of ferrous sulfate heptahydrate and 100 mL of distilled water into the reaction flask and stir to dissolve;
[0144] 0.1g of concentrated sulfuric acid and 0.1g of iron powder were added to the ferrous sulfate solution at once, the temperature was controlled at 30°C, stirred for reaction for 1 hour, filtered, and the filtrate was added to the sodium citrate solution at a rate of 20mL / min through a constant pressure dropping funnel. After the addition was completed, 2.9g of sodium bisulfite was added, and the temperature was raised to 85°C for reaction for 70 minutes; after the reaction was completed, filtered, the filtrate was concentrated under reduced pressure, and vacuum dried at 50°C for 9 hours to obtain 76.4g of yellow solid, with a yield of 74.8%. It can be seen that the repeatability of the modified method is poor, and it is difficult to repeat the experiment to obtain the yield recorded therein.
[0145] This method requires the reaction solution to be concentrated under reduced pressure. Since the solvent is water, the required concentration temperature is high and the time is long, which greatly increases the production time and production cost.
[0146] Table 1 Comparison of experimental operation and test results
[0147] Standard / Operation Internal Control Standards Example 1 Comparative Example 1 Comparative Example 2 Iron content 10.0~11.0% 10.6% 10.2% 10.1% ferric iron content ≤0.1% 0.04% 0.19% 0.28% chloride ≤0.1% ≤0.1% ≤0.1% ≤0.1% Sulfate ≤0.3% ≤0.3% ≤0.5% ≤0.5% Cobalt (Co) content 5ppm 1.0ppm 4.7ppm 5.0ppm Nickel (Ni) content 10ppm 4.2ppm 9.4ppm 16.6ppm Zinc (Zn) content 5ppm 0.2ppm 1.5ppm 8.3ppm Drying temperature / 50℃ 50℃ 50℃ Drying time / 3 hours 6 hours 9 hours Characteristics / Light green crystal Light green crystal Yellow solid
[0148] Table 2 Comparison of quality standards
[0149] standard USP2021 Internal Control Standards Iron content 10.0~11.0% 10.0~11.0% ferric iron content ≤0.25% ≤0.1% chloride ≤0.1% ≤0.1% Sulfate ≤0.5% ≤0.3% Cobalt (Co) content 5ppm 5ppm Nickel (Ni) content 20ppm 10ppm Zinc (Zn) content 10ppm 5ppm
[0150] The above quality test results show that the product quality of Comparative Example 2 cannot meet the requirements of the USP2021 standard, and the trivalent iron exceeds the standard; the product quality of Comparative Example 1 basically meets the requirements of the USP2021 quality standard, but neither can meet the requirements of our company's internal control standards, especially the requirements for heavy metal limits. In the treatment stage of Example 1, the operation process of washing away impurities by reflux of ethanol makes the drying time shorter and the energy consumption lower, and reduces the problems of long drying time, easy agglomeration of products, easy yellowing of products, and easy excess of trivalent iron in the drying process of Comparative Examples 1 and 2.
[0151] In summary, the method of the present invention has a yield of 88-95%, the iron content of the obtained high-purity sodium ferrous citrate is 10.0-11.0%, the trivalent iron content is less than 0.1%, and other test results meet the requirements of pharmacopoeias of various countries. The method has high industrial feasibility and can meet the medicinal needs of sodium ferrous citrate.
[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing sodium ferrous citrate, characterized in that: include: (1) adding an aqueous ferrous sulfate solution to an aqueous sodium citrate solution, and adding ascorbic acid, replacing the reaction system with an inert gas environment, heating the reaction, cooling and centrifuging to obtain a crude sodium ferrous citrate product; (2) heating the crude sodium ferrous citrate product in 85%-95% by mass ethanol under reflux for 15-20 minutes, then filtering while hot, rinsing and drying the filter cake to obtain sodium ferrous citrate; In step (1), the preparation method of the ferrous sulfate aqueous solution comprises: adding iron powder to dilute sulfuric acid in batches, then adding ferrous sulfide, and filtering after the reaction is complete to obtain the ferrous sulfate aqueous solution; the molar feed ratio of the iron powder to sodium citrate is 1.0:(2.0-3.0), the molar feed ratio of the iron powder to the dilute sulfuric acid is (1.0-1.3):1.0, the feed amount of the ferrous sulfide is 0.5%-2.0wt% of the feed amount of the iron powder; the feed amount of the ascorbic acid is 0.3-1% of the mass of the iron powder; In step (2), the heating reflux temperature is 75-80° C., and the amount of ethanol used is 2-5 times the mass of the crude sodium ferrous citrate product.
2. The method for preparing sodium ferrous citrate according to claim 1, characterized in that: The crude sodium ferrous citrate product is heated to reflux in 85% by mass ethanol for 15 to 20 minutes.
3. The method for preparing sodium ferrous citrate according to claim 1, characterized in that: The amount of ethanol used is 2.5 to 3.0 times the mass of the crude sodium ferrous citrate product.
4. The method for preparing sodium ferrous citrate according to any one of claims 1 to 3, characterized in that: The heating reaction temperature is 80°C to 110°C; the heating reaction time is 2 to 4 hours; And / or, the dissolution temperature of the sodium citrate aqueous solution is 85-110°C.
5. The method for preparing sodium ferrous citrate according to claim 4, characterized in that: The temperature of the heating reaction is 90°C to 110°C; And / or, the dissolution temperature of the sodium citrate aqueous solution is 95-105°C.
6. The method for preparing sodium ferrous citrate according to claim 5, characterized in that: The temperature of the heating reaction is 95°C to 105°C.
7. The method for preparing sodium ferrous citrate according to claim 1, characterized in that: The molar feed ratio of the iron powder to sodium citrate is 1.0:(2.3-2.5).
8. The method for preparing sodium ferrous citrate according to claim 1, characterized in that: The molar feed ratio of the iron powder to the dilute sulfuric acid is (1.05-1.1):1.0; And / or, the concentration of the dilute sulfuric acid is 5-20wt%.
9. The method for preparing sodium ferrous citrate according to claim 8, characterized in that: The concentration of the dilute sulfuric acid is 10-15 wt %.
10. The method for preparing sodium ferrous citrate according to claim 1, characterized in that: The feeding amount of the ferrous sulfide is 0.8% to 1.0wt% of the feeding amount of the iron powder.
Citation Information
Patent Citations
Mutual separation of zirconium and hafnium
JP1982051129A
Preparation method of sodium ferrous citrate
CN114436811A